Revision of the Australian species of Aka White, 1879 (Fulgoromorpha: Cixiidae) with the description of a new genus - Löcker, Birgit (Zootaxa, 2015)
The Australian species of the genus Aka White are revised. Seven new species are described: A. balma sp. nov., A. dobsonensis sp. nov., A. gwana sp. nov., A. issidopsis sp. nov., A. kuraka sp. nov., A. pirri sp. nov., A. sorellensis sp. nov. Adding to those the 5 species solely occurring in New Zealand, we have a total number of 14 species in Aka. The types of A. hardyi Muir, 1931 and part of the type series including the holotype of A. tasmani Muir, 1931 are declared lost. However, based on the original descriptions and the remaining type material, these species have been matched with new material examined and are redescribed in this paper. Neotypes are designated for A. hardyi and A. tasmani. A new monotypic genus Yanganaka gen. nov. is described from Australia. Based on characters such as the general shape of the body as well as a forked frontal carina it appears to be closely related to Aka and the New Zealand genus Chathamaka Larivière, 1999. Yanganaka ariecornia sp. nov. is described and illustrated. An identification key to differentiate between the two genera occurring in Australia, Aka and Yanganaka, is provided. Information on how to distinguish Chathamaka from the latter two genera, as well as a key to identify all Australian species of Aka is presented. Host plant associations are discussed which support the hypothesis that Aka is a Gondwanan relict.